Pengaruh Disiplin Kerja, Budaya Organisasi dan Stres Kerja Terhadap Kinerja Pegawai Dinas Perdagangan dan Perindustrian Boyolali - Tsani Said Rahayu; Lamidi (Teewan Journal Solutions, 2026)
The phenomenon of this research, the less than optimal performance of employees at the Boyolali Trade and Industry Service, is marked by a decline in employee performance in 2023 and 2024. The factors causing the decline in employee performance include work discipline, organizational culture and work stress. The purpose of this study (1) to analyze the significance of the influence of work discipline on the performance of employees of the Boyolali Trade and Industry Service, (2) to analyze the significance of the influence of organizational culture on the performance of employees of the Boyolali Trade and Industry Service, (3) to analyze the significance of the influence of work stress on the performance of employees of the Boyolali Trade and Industry Service. The population of this study was all employees of the Boyolali Trade and Industry Service, with a total of 60 people. This study used saturated sampling, namely taking all members of the population as samples. The data collection technique used a questionnaire assessed on a 5-point Likert scale. The data analysis technique used multiple linear regression analysis. The results of the analysis show that (1) Work discipline has a significant effect on the performance of employees of the Boyolali Trade and Industry Service, indicated by p value (0.012) < 0.05, thus hypothesis 1 is proven. (2) Organizational culture has a significant effect on the performance of employees of the Boyolali Trade and Industry Service, indicated by p value (0.000) < 0.05, thus hypothesis 2 is proven. (3) Work stress has a significant effect on the performance of employees of the Boyolali Trade and Industry Service, indicated by p value (0.002) < 0.05, thus hypothesis 3 is proven.